Suitability of Apricot for Dried Fruit Production by Combined Technology - Rahović, Dragan; Keserović, Zoran; Stanković, Slađan; Bakić, Ivana; Maslovarić, Marijana; Kovačević, Vlado; Čolić, Slavica D (Journal of Agricultural Sciences (Belgrade), 2021)
The apricot is considered as one of the most delicious temperate fruit, highly appreciated as stone fruit but also a valuable raw material for processing. The Republic of Serbia is one of the leading apricot producers in the Southeast Europe, but assortment is limited by small number of cultivars harvested in the season of ‘‘Magyar kajszi’. In order to introduce the most suitable cultivars in the production, having high yield and high quality for consumption and various forms of processing, introduced and domestic cultivars have been intensively studied. In Serbia apricots are mostly marketed fresh, but demand for dried fruits with high quality is increasing. To preserve the nutritional and sensory quality of fresh apricots, choosing the best drying technique is significant, and the most preferred technique is reduction of moisture through convective drying. The aim of the paper was to compare the potential of the apricot cultivars ‘‘Magyar kajszi”, “Novosadska rodna”, “NS-4” and “NS-6” for dried fruit production by two phase technology - combined osmotic and convective drying, as well as the profitability of apricot drying on small family farms. Cultivars “NS-4” and “Novosadska rodna” showed suitability for combined drying technology. The highest score in the sensory evaluation of the dried apricots was given to “NS-4”, and then to “Novosadska rodna”. The results indicate that combined osmotic and convective drying of apricot rather than selling fresh fruits can be a profitable and important added value tool for small family farms.
Keywords: fruit, osmotic and convective drying, profitability, Prunus armeniaca